Strategi Efektif Komunikasi Bisnis Dalam Menangani Keluhan Pelanggan Pada Aplikasi Tiktokshop - Hasby, Muhammad; Hidayana, Nugrhainy; Agustina, Putri; Mariska, Refi; Suhairi , Suhairi (CV. ITTC INDONESIA, 2023)
It is hoped that this research can identify and examine appropriate procedures in business correspondence that can be used to determine client complaints in the Tiktokshop application. The Tiktokshop application is now one of the most widely used e-commerce platforms between buyers and sellers in today's digital era. However, the problem of customer complaints is also growing as a result of the rapid growth of platform users and transactions. This study uses a subjective examination strategy by leading meetings from top to bottom with various Tiktokshop clients and dissecting information using substance investigation techniques. The results of the examination show that an effective business communication strategy for dealing with customer complaints on the Tiktokshop application consists of several important steps. First, it is important to have a well-trained and responsive customer support team. This team must respond quickly to customer complaints and provide the right solutions. Second, effective communication through the Tiktokshop platform itself is also important. The use of private messages or comments under posts can be used to interact directly with customers and provide real-time problem solutions. When dealing with customer complaints on the Tiktokshop application, an effective business communication strategy includes quick responses, effective cross-platform communication, an empathetic approach, and a long-term relationship building system. This study contributes to understanding the importance of effective business communication in handling customer complaints in the fast-growing e-commerce era.